Prevalence of cholelithiasis in a Turkish population sample of postmenopausal women - Rana KARAYALÇIN,; Volkan GENÇ,; Ahmet Serdar KARACA,; Gülnur ÖZAKŞİT, (Turkish Journal of Gastroenterology, 2019)
Background/aims: Gallstone disease is a global health problem worldwide. Potential risk factors for gallstone disease have not been well established except for age and gender. We aimed to investigate the prevalence and potential risk factors for gallstone disease in a population of postmenopausal women.Methods: A detailed Turkish questionnaire was prepared, and 474 of 502 postmenopausal women seen at the menopause clinic of Dr. Zekai Tahir Burak Hospital were included in the study. Sociodemographic, medical and reproductive characteristics were analyzed. Subjects were divided into two groups. The gallstone disease group (Group 1, n=73) was defined by both prior histories of gallstones diagnosis or cholecystectomy in the postmenopausal period and the presence of current sonographically diagnosed gallstones; Group 2 (n=401) included women with no gallstone disease.Results: The present study found a 15.4% prevalence rate of cholelithiasis in a Turkish population sample of postmenopausal women. The demographic characteristics were similar between the two groups. The mean gravidity was 5.25 in Group 1 and 4.9 in Group 2. The number of subjects with past oral contraceptive use was 17 (23.3%) in Group 1 and 56 (13.9%) in Group 2. The number of women who took hormone replacement therapy was 40 (54.8%) in Group 1 and 222 (55.3%) in Group 2. There was no significant difference related to mean total cholesterol levels (216.5±44.9 mg/dl versus 215.9±44.3 mg/dl; p=0.915) and mean triglycerides (134.5±54.8 mg/dl versus 143.2±77 mg/dl; p=0.202) between the two groups.Conclusions: No risk factors for developing gallstones were determined among the evaluated parameters in postmenopausal women.